Peculiarities and Rules of Artistic Translation - Djalolov Zafarjon (Journal of Geography, Regional Planning and Development, 2024)
To translate a work of art, it is necessary to know the vocabulary richness of the language, the synonyms and homonyms, professional terms, dialect-specific, outdated and vulgar words, caresses and diminutives, evils, Proverbs, matals and phrases, as well as the musicality, tonality, versatility, pronunciation norms of the language, exaggeration and diminutives, humorous forms. The scientific description of the artistic translation is such that it is important to give the word not by word, but by meaning, the image by image, the humor-by humor. In this article, opinions and reflections are made on the peculiarities and rules of the artistic translation.